Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1210/jc.2018-00746
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-203 Modulates Aldosterone Levels and Cell Proliferation by Targeting Wnt5a in Aldosterone-Producing Adenomas

Abstract: We have demonstrated that attenuated miR-203 expression in APAs increases aldosterone production and the tumorigenesis of adrenal cells by activating the Wnt5a/β-catenin pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…CNO-treated mice were sis (54). Within the ZG, most cells are positive for both β-catenin and Cyp11b2 (52), and it has been suggested that Wnt/β-catenin signaling can control aldosterone production (57,61). Activating mutations in CTNNB1, the gene that encodes β-catenin, have also been described in a small subset of human aldosterone-producing adenomas (62)(63)(64)(65).…”
Section: Methodsmentioning
confidence: 99%
“…CNO-treated mice were sis (54). Within the ZG, most cells are positive for both β-catenin and Cyp11b2 (52), and it has been suggested that Wnt/β-catenin signaling can control aldosterone production (57,61). Activating mutations in CTNNB1, the gene that encodes β-catenin, have also been described in a small subset of human aldosterone-producing adenomas (62)(63)(64)(65).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with previous reports, our study also found that Wnt5a level was significantly increased in glioma cell lines and tissues. Up-regulation of Wnt5a can induce Wnt/β-catenin activation (Peng et al 2018;Bo et al 2013). The mechanism by which Wnt signaling pathway regulating tumorigenesis involves many aspects such as signal transduction, cell cycle, cell proliferation migration and apoptosis (He et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, miRNA-mediated activation of the Wnt/β-catenin pathway was shown in the pathogenesis of APAs [62]. It is well known, that the Wnt/β-catenin pathway is involved in the regulation of cell proliferation and steroid biosynthesis in human adrenocortical cells [63][64][65][66].…”
Section: Reviewmentioning
confidence: 99%
“…With a high-throughput miRNA-microarray method Peng et al have found two Wnt/β-catenin pathway-related miRNAs, hsa-miR-375 and hsa-miR-203 as the most significantly underexpressed miRNAs in APAs relative to adjacent normal adrenal tissues [62]. Moreover, expression of hsa-miR-203 has been negatively correlated with the plasma aldosterone level in APA patients [62]. In breast cancer cells, the epigenetical silencing of hsa-miR-203 via hypomethylation has led to the activation of the Wnt/β-catenin pathway [67].…”
Section: Reviewmentioning
confidence: 99%